Simulation Design of Dental Practice Medical Waste Management Using Dynamic System Model Approach - Oktavia Dewi; Nila Puspita Sari; Raviola Raviola; Herniwanti Herniwanti; Novita Rany (Jurnal Penelitian Pendidikan IPA, 2022)
Medical waste from dental practice is harmful to life and the environment. Previous studies reported that the total medical solid waste generated by dental practices in Pekanbaru City was 4.62 kg/day with an average of 0.3 kg Â± 0.07 kg/day. Based on the type of waste generated, 69% is infectious waste, 27% is toxic waste, and 4% is radioactive waste. The purpose of the study was to analyze the medical waste generated and the environmental costs incurred by dentists using several scenarios of medical waste management policy intervention. The method used is a simulation model with a dynamic system approach. Simulations were carried out from 2018 to 2047. The results of the study obtained a percentage reduction for 30 years, it was found that the combination of providing training and cooperation with the waste management party had the largest decrease of 41.9%. The biggest decrease in environmental costs was the combined scenario of 99.69%, followed by the 99.62% cooperation scenario and 19.5% training. The most effective self-care solid medical waste management model is the scenario 3 model because it can reduce the waste generated and also reduce costs. Â